PENGELOLAAN RETRIBUSI PARKIR DALAM MENINGKATKAN PENDAPATAN ASLI DAERAH KOTA DENPASAR (Studi Kasus : Perusahan Umum Daerah Bhukti Praja Sewakadarma) - Marpaung, Puji Lestari; Wirantari, I Dewa Ayu Putri; Prabawati, Ni Putu Anik (CITIZEN CHARTER, 2023)
A regional levy is a regional levy as payment for services or the issuance of specific permits provided or granted by regional governments specifically for personal or business benefit, the items and contributions of which are linked to regional revenue growth. to increase Park fees, one of the unique sources of income from the community, is managed by the Bukti Praja Sewakadharma Regional Authority. The management of parking fees to increase the income of the city of Denpasar itself is included in Denpasar Municipal Ordinance No. 19 of 2011 in retaliation against public street parking services. In order to increase the original local income of Denpasar City, it is necessary to increase the park usage fee income, which will affect the local development. The research method used is a descriptive qualitative method. Data collection techniques used are observations, interviews and documentation. The results of the study show that the management of parking fees on public roads in Denpasar City is not optimized. This is illustrated by the fact that there are still valets who charge parking fees that do not correspond to the accuracy of the rates stated in the regulations, and that many illegal valets are still active. The purpose of this study is to clarify how parking fee management in Denpasar City increases the original area using the management theory of G.R Terry (2018). Keywords: Management, Local Revenue, Parking Retributio